1974
DOI: 10.1128/jb.118.2.590-597.1974
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Alanine Dehydrogenase in Bacillus licheniformis

Abstract: Cell extracts of Bacillus licheniformis were found to contain nicotinamide adenine dinucleotide (NAD)-dependent L-alanine dehydrogenase (ADH) (Lalanine:NAD oxidoreductase, EC 1.4.1.1)'. High specific activities (3.5 to 6.0 IU/mg of protein) were found in extracts of cells throughout growth cycles only when L-alanine served as the primary source of carbon or carbon and nitrogen.Specific activities were minimal (0.02 to 0.04 IU/mg of protein) during growth on' glucose, but increased at least sevenfold during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…L-Alanine dehydrogenase (ADH, EC 1.4.1.1) is a key enzyme in the catabolism of L-alanine [1][2][3]. It has been suggested that, under conditions with high external ammonia concentrations, ADH activity could also account for NH + -assimilation in organisms lacking glutamate dehydrogenase (EC 1.4.1.2), as for example, Bacillus species [4], bluegreen bacteria [5] and the facultative phototrophic bacterium, Rhodopseudomonas (Rps.)…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…L-Alanine dehydrogenase (ADH, EC 1.4.1.1) is a key enzyme in the catabolism of L-alanine [1][2][3]. It has been suggested that, under conditions with high external ammonia concentrations, ADH activity could also account for NH + -assimilation in organisms lacking glutamate dehydrogenase (EC 1.4.1.2), as for example, Bacillus species [4], bluegreen bacteria [5] and the facultative phototrophic bacterium, Rhodopseudomonas (Rps.)…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…In Bacillus species this enzyme is known to play a key role in the generation of pyruvate as energy source during sporulation (5,6). The kinetic properties of the enzyme have been elucidated (7), together with the mechanism (8) and the limiting steps of the catalysis (9).…”
Section: Reactionmentioning
confidence: 99%
“…The Hut enzymes were assayed by using the methods of Lund and Magasanik [21] and Chasin and Magasanik [16], as described previously [17]. Alanine dehydrogenase was assayed by using the method of McCowen and Phibbs [22], and arginase by the method of Ratner [23]. One unit of alanine dehydrogenase and of arginase activity is defined as the amount of enzyme that gives an increase in absorbance of 0.1 at 340 and 515 nm, in 2.5 and 20 min and at 22 and 37°C, respectively.…”
Section: Enzyme Assaysmentioning
confidence: 99%